2019
DOI: 10.1007/s10797-019-09540-1
|View full text |Cite
|
Sign up to set email alerts
|

Tax policy and entrepreneurial entry with information asymmetry and learning

Abstract: We study a market with entrepreneurial and worker entry where both entrepreneurs' abilities and workers' qualities are private information. We develop an agent-based computable model to mimic the mechanisms described in a previous analytical model (Boadway and Sato in Int Tax Public Finance 18(2):166-192, 2011). Then, we introduce the possibility that agents may learn over time about abilities and qualities of other agents, by means of Bayesian inference over informative signals. We show how such different ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(28 reference statements)
0
2
0
Order By: Relevance
“… Yong (2012) conducted a simulation study on the issue of information asymmetry and found that investors would choose the method of average valuation for investment activities in the case of asymmetric information, which would affect the development of some enterprises with high demand for cash flow; however, for enterprises with low demand for cash flow, over-investment would occur ( Yong, 2012 ; Abidoye et al, 2019 ). d’Andria (2019) focused on the information asymmetry in the credit and labor markets at the same time. Considering the learning over time and its impact on tax and subsidy policies, simulation analysis was utilized to test the impact of tax policies on the entrepreneurs and subsidies on labor incomes ( d’Andria, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… Yong (2012) conducted a simulation study on the issue of information asymmetry and found that investors would choose the method of average valuation for investment activities in the case of asymmetric information, which would affect the development of some enterprises with high demand for cash flow; however, for enterprises with low demand for cash flow, over-investment would occur ( Yong, 2012 ; Abidoye et al, 2019 ). d’Andria (2019) focused on the information asymmetry in the credit and labor markets at the same time. Considering the learning over time and its impact on tax and subsidy policies, simulation analysis was utilized to test the impact of tax policies on the entrepreneurs and subsidies on labor incomes ( d’Andria, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“… d’Andria (2019) focused on the information asymmetry in the credit and labor markets at the same time. Considering the learning over time and its impact on tax and subsidy policies, simulation analysis was utilized to test the impact of tax policies on the entrepreneurs and subsidies on labor incomes ( d’Andria, 2019 ). Based on the causality test of repurchase information and enterprise earnings, Lee and Mauck (2018) connected the informed repurchase to the asymmetry of corporate information and proposed a new informed repurchase measure.…”
Section: Literature Reviewmentioning
confidence: 99%